Living‐donor kidney transplantation for a patient with hypoparathyroidism, deafness, and renal dysplasia syndrome. Issue 6 (27th July 2020) - Nishimura, Nobutaka; Hori, Shunta; Omori, Chihiro; Miyake, Makito; Anai, Satoshi; Torimoto, Kazumasa; Aoki, Katsuya; Tanaka, Nobumichi; Yoneda, Tatsuo; Fujimoto, Kiyohide
Abstract : Introduction: Hypoparathyroidism, sensorineural deafness, and renal dysplasia syndrome is an autosomal dominant rare genetic disease. Some patients with hypoparathyroidism, sensorineural deafness, and renal dysplasia syndrome may present with renal calcification (nephrocalcinosis) and disorder. We report the first case of living‐donor kidney transplantation for a patient with hypoparathyroidism, sensorineural deafness, and renal dysplasia syndrome. Case presentation: This case pertains to a 26‐year‐old woman who was diagnosed with congenital hypoparathyroidism 1 month after birth, following which vitamin D supplementation was initiated. In 20XX, she developed nephrocalcinosis and was confirmed to have a GATA3 mutation; hence, she was diagnosed with hypoparathyroidism, sensorineural deafness, and renal dysplasia syndrome. In 20XX + 7, ABO‐incompatible living‐donor kidney transplantation was performed. Her renal function improved, and graft calcification was not observed. Conclusion: Over intake of vitamin D caused nephrocalcinosis. The renal function was improved after living‐donor kidney transplantation and the patient's serum calcium levels normalized without vitamin D supplementation. Therefore, kidney transplantation should be considered a treatment option for patients with hypoparathyroidism, sensorineural deafness, and renal dysplasia syndrome.